2011
DOI: 10.1039/c0ob00467g
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of the anticancer β-elemene and other bioactive elemanes from sustainable germacrone

Abstract: Highly efficient preparations of anticancer β-elemene and other bioactive elemanes were carried out using the natural product germacrone as a renewable starting material. The syntheses were achieved in only 3-5 steps with excellent overall yields (43-54%). An enantioselective approach to these molecules is also described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Germacrone treatment increases Bok expression and cytochrome c release from the mitochondria without affecting Bcl-2, Bcl-xL, Bax, and Bim protein expression and induces the cleavage of PARP and the activation of caspase-3, caspase-7, and caspase-9 ; however, the germacrone concentration required to achieve its anti-cancer properties is relatively high (i.e., nearly 200 mM) . Recently, Barrero et al (2011) reported that the synthesis of b-elemene and other bioactive elemenes is possible using germacrone as a renewable starting material and that the synthesis is achieved in only three to five steps with excellent overall yields. This finding suggests that germacrone may be used as a viable starting material for elemene synthesis.…”
Section: Germacronementioning
confidence: 99%
“…Germacrone treatment increases Bok expression and cytochrome c release from the mitochondria without affecting Bcl-2, Bcl-xL, Bax, and Bim protein expression and induces the cleavage of PARP and the activation of caspase-3, caspase-7, and caspase-9 ; however, the germacrone concentration required to achieve its anti-cancer properties is relatively high (i.e., nearly 200 mM) . Recently, Barrero et al (2011) reported that the synthesis of b-elemene and other bioactive elemenes is possible using germacrone as a renewable starting material and that the synthesis is achieved in only three to five steps with excellent overall yields. This finding suggests that germacrone may be used as a viable starting material for elemene synthesis.…”
Section: Germacronementioning
confidence: 99%
“…39 A recent study revealed that b-elemenal was appreciably more potent than b-elemene in suppressing nonsmall cell lung cancer growth and proliferation. 39 A recent study revealed that b-elemenal was appreciably more potent than b-elemene in suppressing nonsmall cell lung cancer growth and proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 2, 4,a nd 5 are assumed to be produced from a-cyperone or cyperol, [16b] even thoughc yclic ether moieties were not formed in 4 and 5.O nt he other hand, some isolated compoundsa re assumed to be produced by unexpected reactions. For example, compound 6 is produced from germacrone, [18d] a constituent of C. zedoaria,b ys equential reduction, etherification, cyclization, and additional Cope rearrangement [21] (Scheme3B). Compounds 7 and 8 are produced from curzerenone by sequential reduction,e therification, and bicyclization causedb yt andemM izoroki-Heck reactions (Scheme3C).…”
Section: Isolation and Structure Elucidation Of Phenolic Meroterpenoidsmentioning
confidence: 99%